ANALISIS RASIO LIKUIDITAS, SOLVABILITAS DAN PROFITABILITAS DALAM MENILAI KINERJA KEUANGAN PT. VICTORIA CARE INDONESIA. Tbk YANG TERDAFTAR PADA BURSA EFEK INDONESIA PERIODE TAHUN 2020 SAMPAI DENGAN 2022 - Apriana, Susi; Setianti, Novita; Purbasari, Wika (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2024)
PT Financial Performance Victoria Care Indonesia.tbk is the main contact in thisinvestigation. Performance measurement is based on measuring liquidity, solvency andbprofitability ratios for the 2020-2022 period. The research approach was carried out using quantitative research methods and the data was analyzed using primary data using the SPSS measuring tool. The data used is the financial report of the company PT. Victoria Peduli Indonesia. Tbk 2020-2022 received from www.idx.co.id. From the data analyzed, observed and discussed, it shows that from the calculation of the liquidity ratio which consists of the Current Ratio, PT Victoria Care (VICI) has a ratio calculation for 2020, 2021 and 2022 with a ratio assessment of more than 1 which indicates the company able to pay debts well, from the calculation of the Solvency Ratio PT Victoria Care (VICI) with the Debt Ratio has a ratio assessment of more than 1 which shows good results because the value of the company's assets is still higher than debt, which means that not all of the company's assets are financed by debt and from the calculation The Profitability Ratio of PT Victoria Care (VICI) with Return on Assets has a good assessment because it has a ratio calculation result of above 5.98%. This means that PT Victoria Care (VICI) is able to get a good net profit (Net Income) in each year but The calculation of the ROA ratio every year fluctuates, namely an increase from 15% to 18% in 2020, then a decrease from 2022 to 8%. This indicates that PT Victoria Care (VICI) cannot make maximum use of the net profits from all the company assets it owns.